Internet factors influencing generations Y and Z in Australia and Portugal: A practical study - Issa, Tomayess; Isaias, P. (Elsevier Ltd, 2016)
This practical study aims to enrich the current literature by providing new practical evidence of the positive and negative influence factors of the Internet on generations (Gens) Y and Z in Australia and Portugal. The Internet has become a powerful force among these Gens in relation to communication, cooperation, collaboration and connection, but numerous problems from cognitive, social and physical developments' perspective are developed throughout the Internet usage. A quantitative approach was used to collect new, practical evidence from 180 Australian and 85 Portuguese respondents, with a total of 265 respondents completing an online survey. This study identifies new positive factors to the Internet usage, as problem-solving skills, proactive study, information gathering, and awareness globally and locally; communication and collaboration with their peers and family were improved and enhanced. Alternatively, this study identifies new negative factors as physical contact and physical activities were prevented, thinking, concentrating and memory skills were reduced, depressed and isolated, laziness having increased, nevertheless; the Internet encourages Gens Y and Z to play physical and virtual games (e.g. Wii). Finally, this study concluded that the Internet is becoming an essential part of the everyday routines and practices of Gens Y and Z.